rezolvati ecuatiile:
5x+2=3x-2
2x-1(supra) 1 - 3x-3(supra) 3 = x-1 (supra) 4
√7 x (x-2)+7x = √7x x (√7 - 2)
Răspunsuri la întrebare
Răspuns de
1
5x+2=3x-2
5x-3x=-2-2
2x=-4
x=-4/2
x=-2
2x-1/1-3x-3/3=x-1/4
24x-12-36x-36=12x-12
24x-36x-12x=12+36-12
-24x=36
x=-36/24
x=-3/2
√7*(x-2)+7x=√7*(√7-2)
√7x-2√7+7x=7-2√7
√7x+7x=2√7+7-2√7
√7x+7x=7
5x-3x=-2-2
2x=-4
x=-4/2
x=-2
2x-1/1-3x-3/3=x-1/4
24x-12-36x-36=12x-12
24x-36x-12x=12+36-12
-24x=36
x=-36/24
x=-3/2
√7*(x-2)+7x=√7*(√7-2)
√7x-2√7+7x=7-2√7
√7x+7x=2√7+7-2√7
√7x+7x=7
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba rusă,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Ed. tehnologică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă